Controlled, Randomized Study of Pain Levels in Subjects Treated with Calcium Hydroxylapatite Premixed with Lidocaine for Correction of Nasolabial Folds - MARMUR, ELLEN; GREEN, LAWRENCE; BUSSO, MARIANO (Dermatologic surgery, 2010)
BACKGROUND Calcium hydroxylapatite (CaHA) has been administered after nerve block injection of anesthetic agents. OBJECTIVES This prospective, randomized, split‐face, single‐blind study (50 subjects) assessed the pain reduction, safety, and effectiveness of premixing CaHA with 2% lidocaine for the treatment of nasolabial folds (NLFs). METHODS AND MATERIALS Subjects were randomized to receive treatment with CaHA alone in one NLF (control) and with CaHA premixed with lidocaine in the other NLF (treatment). Subjects completed pain assessments using a validated visual analog scale at specified time points immediately after injection, 1 hour after injection, and 1 month later. Subjects also indicated relative pain experience and preference assessments. Investigators completed aesthetic assessments at 2 weeks and 1 month. Subjects and investigators recorded adverse events. RESULTS Subjects reported statistically significantly less pain in the treatment fold than in the control fold and expressed unanimous preference for the treatment injection over the control. Aesthetic results were essentially equivalent for both treatments. CONCLUSION Investigators concluded that CaHA premixed with lidocaine results in significant pain reduction during dermal filler injection while maintaining the aesthetic improvement of CaHA without lidocaine and demonstrating comparable local transient adverse events for treatment and control. BioForm Medical (San Mateo, CA) provided the soft tissue filler, lidocaine, and other necessary supplies used in this study. All authors are members of the Bioform Medical Education Faculty.